Network frontier as a metaphor and myth - Plotichkina, N.V.; Dovbysh, E.G. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2017)
This article considers spatial metaphors of the Internet and the possibility to extrapolate the frontier thesis of F. Turner on the electronic space. The authors believe that information and communication technologies and the digital world have become new spaces for the expansion of states or individuals. That is why there are ongoing scientific debates on the limits and potential of western and electronic frontiers’ metaphors for analytical description of the digital space. The metaphor of the Internet as a western frontier is quite controversial; many authors prefer the electronic frontier analogy as more heuristic and valid for constructing metaphors of the digital reality. The network frontier is defined as a dynamic, elastic and permeable border of social and cultural practices of the network society. The authors estimate the heuristic potential of the concept ‘network frontier’ developed on the basis of integration of the frontier theory and the concept ‘network society’, taking into account the effects of globalization for the study of elastic, permeable and movable border of the network landscape. In the digital world, the spatiality transforms, the geography of the Internet network determines the metamorphosis of the frontier as a contact zone between online and offline spaces, which is dynamic, innovative, encourages mobility, and its permeability depends on the digital competence of citizens. The authors explain the mythology of western and electronic frontier; name the main network frontier myths related to the rhetoric of western frontier myth; describe the main components of the western frontier myth associated with the idea of American exceptionalism; and conclude with the identification of nowadays myths about frontier-men and the online space they master.